2023
DOI: 10.3389/ijph.2022.1605363
|View full text |Cite
|
Sign up to set email alerts
|

Social Media Overload and Anxiety Among University Students During the COVID-19 Omicron Wave Lockdown: A Cross-Sectional Study in Shanghai, China, 2022

Abstract: Objectives: The increase in the intensity of social media use during the COVID-19 lockdown has affected mental health. Therefore, it is of practical implications to explore the association between social media overload and anxiety and the underlying mechanisms.Methods: Using data from 644 university students during the COVID-19 blockade in Shanghai from March to April 2022, the chain mediation model of information strain and risk perception of omicron between social media overload and anxiety was then tested u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 71 publications
(79 reference statements)
2
5
0
Order By: Relevance
“…The need for workers to be available at all times goes beyond the workplace and working hours. This evidence is in line with prior findings of Wang, Xu and Xie 62 and Tandon et al 107 and Taboroši et al 9 …”
Section: Discussionsupporting
confidence: 93%
“…The need for workers to be available at all times goes beyond the workplace and working hours. This evidence is in line with prior findings of Wang, Xu and Xie 62 and Tandon et al 107 and Taboroši et al 9 …”
Section: Discussionsupporting
confidence: 93%
“…Chinese government adopted a zero-COVID strategy and took strict lockdown measures during the COVID-19 [76]. Multiple studies have shown that strict lockdown policies increase people's psychological burden [76,77]. The present study provides experimental evidence for the psychological health status of college students in this context.…”
Section: The Relationship Between Risk Perception and Depression Amongmentioning
confidence: 67%
“…Chinese government adopted a zero-COVID strategy and took strict lockdown measures during the COVID-19 [76]. Multiple studies have shown that strict lockdown policies increase people's psychological burden [76,77].…”
Section: The Relationship Between Risk Perception and Depression Amongmentioning
confidence: 99%
“…From the media selection perspective, negative emotions affect the decision process differently, including choosing media to obtain information in a crisis (Jin, 2009; Lerner et al, 2015). Scholars recommend that people limit their time and frequency of use of social media in times of crisis to control negative emotions (Wang et al, 2023). Indeed, many people have blamed social media for fostering negative emotions (Faize & Husain, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%